Pengaruh jumlah sekat vertikal dan debit aliran terhadap viskositas oli pada separator air oli - Qiram, I. (Universitas Mataram, 2017)
Water pollution is a major environment problem. Oil water separator can be used to solve this problem. This research is aimed to get the effect of vertical divider number and fluid flow rate due to oil viscosity. The research is done by experiment using gravity separator. Vertical dividers are varied as 5 and 7. Fluid flow rate is vary as 176,5; 106,6; 53,7 and 33,7 ml/s. Oil 0,5 litre is mixture with 10 litres of water. Oil viscosity is measured with simple flow gravity method. The data is analized statistically using SPSS 17.0. The result shows that vertical divider number and fluid flow rate have effect on oil viscosity.